ANALISIS HUBUNGAN TINGKAT PENDIDIKAN TERHADAP FERTILITAS - Asti Lestari; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Indonesia is a developing country that is still faced with population problems, one of which is population growth. Population growth in Indonesia is quite high, the 2020 census recorded that the population in Indonesia was 270, 20 million people (BPS, 2020). Fertility is one of the factors that greatly influences fertility. Fertility is influenced by demographic and non-demographic factors. An example of a non-demographic factor is a social factor, namely the level of education. A person's final level of education has an influence on fertility. Education can develop potential, develop thinking, and so on. The aim of this research is to analyze the relationship between education level and fertility. The method used is a qualitative method, namely literature study using various reading sources. The research results show that the relationship between education and fertility is negative. Educated people tend to focus on continuing their education or career, so they often marry late or marry at an old age. Marrying at an old age for women certainly affects the age at first marriage. This certainly affects the length of a husband and wife's relationship. Educated people also really consider having a child, because that person really understands the big responsibility of being a parent. They often postpone, limit, and even decide not to have children.